The Sacrality of Water - Andrea Toffolon (Histoire, Médecine et Santé, 2023)
During a plague outbreak, a Marian apparition led to the foundation of a church and monastery in Monteortone, near the famous site of the Paduan baths of Abano. A central element in this narrative—underlined by an early modern printed book—is the sacred hot mineral spring called “acqua della Vergine” (“Virgin’s water”). By looking closely at the various sources that deal with the case of Monteortone, this article investigates the differences between miraculous springs and hot mineral springs in the Christian thought, the different uses of the Abano’s mineral waters and the sacralisation of Monteortone’s mineral spring during the Counter-Reformation. Moreover, it sheds light how the religious and medical aspects of the consumption and representation of mineral waters in early modern Italy overlapped.